DETERMINAN YANG MEMPENGARUHI CASH HOLDING - Lisanto , Jane Christy; Bangun, Nurainun (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to determine the effect of leverage, capital expenditure and sales growth on cash holding in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018-2021. The sample selection technique in this study used purposive sampling technique and the valid data were 111 companies. The data processing in this study uses multiple regression analysis technique and is assited by EViews 12 and Microsoft Excel 2019. The results of this study are leverage and capital expenditure have a positive effect on cash holding, while sales growth has no effect on cash holding. Implication of this research is that companies need to pay attention to the amount of cash holding companies so that the presence of cash in the company is at the optimal point to avoid the company from going bankrupt.